Dispersal in the desert: ephemeral water drives connectivity and phylogeography of an arid‐adapted fish. (3rd October 2015) - Mossop, Krystina D.; Adams, Mark; Unmack, Peter J.; Smith Date, Katie L.; Wong, Bob B. M.; Chapple, David G.
Abstract: Aim: We examine landscape processes shaping the range‐wide phylogeography of a dispersal‐limited, desert‐dwelling fish (the desert goby, Chlamydogobius eremius ) in arid Australia. Location: South‐western Lake Eyre Basin, central Australia. Methods: We obtained sequence data for the mitochondrial cytochrome b gene ( n = 513 individuals) and nuclear genetic markers (51 allozyme loci; n ≥ 128 individuals) to investigate the phylogeographic relationships among 51 populations. Sampling spanned multiple habitat types (permanent desert springs, ephemeral rivers) and sub‐catchments, and the entire distribution of C. eremius and representatives of its sister species, Chlamydogobius japalpa . Phylogeographic analyses (genetic diversity, AMOVA, Tajima's D, W ST, mismatch distribution) were used to explore the distribution and partitioning of mtDNA variation; principal coordinates analysis and neighbour‐joining tree networks were used to explore allozyme variation. Results: Three main genetic groups exist across C. eremius / C. japalpa populations. The geographical distributions of these groups reflected the historical and current confluence point of major rivers in the region. Surprisingly, permanent desert springs did not contain higher genetic diversity than ephemeral rivers. Main conclusions: Genetic structuring of Chlamydogobius populations revealed unanticipated levels of connectivity, indicating that the ephemeral waters of Lake Eyre have allowed gene flow across drainage boundaries and large distances. Phylogeographic breaks reveal that connectivity relies on temporary surface water, while rapid temporal changes in diversity highlight flood‐driven dispersal as the main means of gene flow between localities and habitats. Dispersal pathways reveal that ecological context (life history and tolerance of extreme conditions) has played a key role in shaping observed patterns.